2014
DOI: 10.1007/978-3-319-05029-4_16
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Social Media and IoT to Bootstrap Smart Environments

Abstract: As we move towards an era of Smart Environments, mixed technological and social solutions must be examined to continue to allow users some control over their environment. Realisations of Smart Environments such as Smart Cities and Smart Buildings bring the promise of an intelligently managed space that maximises the requirements of the user while minimising resources. Our approach is to create lightweight Cyber Physical Social Systems that aim to include building occupants within the control loop to allow them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Malaysian internet users are well-known for their frequent use of social networking and time spent on YouTube (Malaysian Communications and Multimedia Commission, 2014). Crowley et al (2014) have used social media (i.e. Twitter) to communicate informational messages with building users, resulting in an energy use reduction of 26 per cent.…”
Section: Resultsmentioning
confidence: 99%
“…Malaysian internet users are well-known for their frequent use of social networking and time spent on YouTube (Malaysian Communications and Multimedia Commission, 2014). Crowley et al (2014) have used social media (i.e. Twitter) to communicate informational messages with building users, resulting in an energy use reduction of 26 per cent.…”
Section: Resultsmentioning
confidence: 99%
“…While these technologies helped in promoting and triggering pro-environmental behaviour, research has shown that they can pose an obstacle especially to those with low ICT skills and/or who are privacy-conscious [36]. For example, [37] achieved a 26% reduction in energy consumption when linking their Eco-feedback system to Twitter to send users suggestions about their energy usage. Conversely, in the GoodDeeds project [38], participants who were new to social media and/ or had a bad experience with it refused to share their energy-related data/ saving activities on it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the examples are the inclusion of users to save energy in smart buildings and environments (Crowley et al 2014) or location-based social media campaigns in combination with various kinds of wearables (Maiorescu et al 2020). Such convergence has been a property of technological evolution for decades and led to continuous improvements in quantitative (e.g.…”
mentioning
confidence: 99%